Metal-free C–H mercaptalization of benzothiazoles and benzoxazoles using 1,3-propanedithiol as thiol source - Xiao, Yan; Jing, Bing; Liu, Xiaoxia; Xue, Hongyu; Liu, Yajun (Beilstein Journal of Organic Chemistry, 2019)
A facile and effective C–H functionalization strategy for the synthesis of 2-mercaptobenzothiazoles and 2-mercaptobenzoxazoles is described. 1,3-Propanedithiol was employed to convert benzothiazoles and benzoxazoles to the corresponding heteroarylthiols in the presence of potassium hydroxide and DMSO. This novel protocol is featured by direct C–H mercaptalization of heteroarenes and a simple reaction system.
Keywords: benzothiazole; benzoxazole; C–H functionalization; mercaptalization; 1,3-propanedithiol

(untitled) - Gill, R. K.; Rawal, R. K.; Bariwal, J. (Arch. Pharm. (Weinheim, Ger.), 2015)

(untitled) - Ranjit, S.; Lee, R.; Heryadi, D.; Shen, C.; Wu, J.; Zhang, P.; Huang, K.-W.; Liu, X. (J. Org. Chem., 2011)

(untitled) - Yarar, S.; Ozturk, I. I.; Banti, C. N.; Panagiotou, N.; Papatriantafyllopoulou, C.; Manoli, M.; Manos, M. J.; Tasiopoulos, A. J.; Hadjikakou, S. K. (Inorg. Chim. Acta, 2018)

(untitled) - El-Asmy, H. A.; Butler, I. S.; Mouhri, Z. S.; Jean-Claude, B. J.; Emmam, M.; Mostafa, S. I. (Inorg. Chim. Acta, 2016)

(untitled) - Mitra, R.; Samuelson, A. G. (Eur. J. Inorg. Chem., 2014)

(untitled) - Prasad, A. V. G. S.; Rao, P. V.; Prasad, P. S. S. (Int. J. Pharm. Res. Scholars, 2014)

(untitled) - Satyendra, R. V.; Vishnumurthy, K. A.; Vagdevi, H. M.; Dhananjaya, B. L.; Shruthi, A. (Med. Chem. Res., 2015)

(untitled) - Defrenza, I.; Catalano, A.; Carocci, A.; Carrieri, A.; Muraglia, M.; Rosato, A.; Corbo, F.; Franchini, C. (J. Heterocycl. Chem., 2015)

(untitled) - Hornung, M. W.; Kosian, P. A.; Haselman, J. T.; Korte, J. J.; Challis, K.; Macherla, C.; Nevalainen, E.; Degitz, S. J. (Toxicol. Sci., 2015)

(untitled) - Testaferri, L.; Tingoli, M.; Tiecco, M. (Tetrahedron Lett., 1980)

(untitled) - Testaferri, L.; Tiecco, M.; Tingoli, M.; Chianelli, D.; Montanucci, M. (Synthesis, 1983)

(untitled) - Shaw, J. E. (J. Org. Chem., 1991)

(untitled) - Liu, Y.; Liu, S.; Xiao, Y. (Beilstein J. Org. Chem., 2017)

(untitled) - Wang, F.; Cai, S.; Wang, Z.; Xi, C. (Org. Lett., 2011)

(untitled) - Varun, B. V.; Prabhu, K. R. (J. Org. Chem., 2014)

(untitled) - Lou, C.; Zhu, N.; Fan, R.; Hong, H.; Han, L.; Zhang, J.; Suo, Q. (Green Chem., 2017)

(untitled) - Deligeorgiev, T. G.; Kaloyanova, S. S.; Lesev, N. Y.; Vaquero, J. J. (Monatsh. Chem., 2011)

(untitled) - Liu, L.; Zhu, N.; Gao, M.; Zhao, X.; Han, L.; Hong, H. (Phosphorus, Sulfur Silicon Relat. Elem., 2016)

(untitled) - Liu, X.; Liu, M.; Xu, W.; Zeng, M.-T.; Zhu, H.; Chang, C.-Z.; Dong, Z.-B. (Green Chem., 2017)

(untitled) - Zhu, X.; Li, W.; Luo, X.; Deng, G.; Liang, Y.; Liu, J. (Green Chem., 2018)

(untitled) - Foye, W. O.; Abood, N.; Kauffman, J. M.; Kim, Y.-H.; Patel, B. R. (Phosphorus Sulfur Relat. Elem., 1980)

(untitled) - Watt, G. W. (J. Org. Chem., 1939)

(untitled) - Liu, Y.; Kim, J.; Seo, H.; Park, S.; Chae, J. (Adv. Synth. Catal., 2015)

(untitled) - Shen, C.; Zhang, P.; Sun, Q.; Bai, S.; Hor, T. S. A.; Liu, X. (Chem. Soc. Rev., 2015)

(untitled) - Lee, C.-F.; Basha, R. S.; Badsara, S. S. (Top. Curr. Chem., 2018)

(untitled) - Dai, C.; Xu, Z.; Huang, F.; Yu, Z.; Gao, Y.-F. (J. Org. Chem., 2012)

(untitled) - Rosario, A. R.; Casola, K. K.; Oliveira, C. E. S.; Zeni, G. (Adv. Synth. Catal., 2013)

(untitled) - Rafique, J.; Saba, S.; Frizon, T. E. A.; Braga, A. L. (ChemistrySelect, 2018)

(untitled) - He, Z.; Luo, F.; Li, Y.; Zhu, G. (Tetrahedron Lett., 2013)

(untitled) - Gandeepan, P.; Mo, J.; Ackermann, L. (Chem. Commun., 2017)

(untitled) - Liu, Y.; Wang, H.; Wang, C.; Wan, J.-P.; Wen, C. (RSC Adv., 2013)

(untitled) - Zhou, A.-X.; Liu, X.-Y.; Yang, K.; Zhao, S.-C.; Liang, Y.-M. (Org. Biomol. Chem., 2011)

(untitled) - Inomata, H.; Toh, A.; Mitsui, T.; Fukuzawa, S.-i. (Tetrahedron Lett., 2013)

(untitled) - Fukuzawa, S.-i.; Shimizu, E.; Atsuumi, Y.; Haga, M.; Ogata, K. (Tetrahedron Lett., 2009)

(untitled) - Popov, I.; Do, H.-Q.; Daugulis, O. (J. Org. Chem., 2009)

(untitled) - Yan, H.; Huang, Z.; Chen, M.; Li, C.; Chen, Y.; Gao, M.; Lei, A. (Org. Biomol. Chem., 2017)

(untitled) - Liu, Y.; Park, S. K.; Xiao, Y.; Chae, J. (Org. Biomol. Chem., 2014)

(untitled) - Le Quéméner, F.; Subervie, D.; Morlet-Savary, F.; Lalevée, J.; Lansalot, M.; Bourgeat-Lami, E.; Lacôte, E. (Angew. Chem., Int. Ed., 2018)

(untitled) - Liu, X. G.; Wu, J. P.; Liang, X. M.; Wang, D. Q. (Chin. J. Org. Chem., 2001)

(untitled) - Zou, L.-H.; Reball, J.; Mottweiler, J.; Bolm, C. (Chem. Commun., 2012)